TAX DEDUCTION THROUGH ZAKAT: AN EMPIRICAL INVESTIGATION ON MUSLIM IN MALAYSIA - Abdullah Al-Mamun; Ahasanul Haque (Share: Jurnal Ekonomi dan Keuangan Islam, 2015)
The aim of this study is to explore the factors which are affecting Muslim consumer's perception towards tax deduction through zakat in Malaysia. A conceptual framework was drawn based on the literature. Six factors were extracted through principal component analysis and SEM was run to test the hypotheses. This research found that halal-haram aspect of Islamic Shariah has a very positive influence on Muslim consumer's perception towards the tax rebate system. In addition, legal consciousness and knowledge about tax and zakat have a positive significant impact on Muslim consumers’ perceptions towards this system. Due to the limited literature available on this subject matter, this study offers unique findings that may help in capitalizing the practices in Muslim countries and to understand their consumers' perception regarding the tax deduction system. In conclusion, zakat institutions in Malaysia will also be better benefitted through this research finding. ========================================================================================================Tujuan penelitian ini adalah untuk menggali faktor- faktor yang mempengaruhi persepsi para konsumen muslim terkait dengan pengurangan pajak melalui zakat di Malaysia. Suatu kerangka konseptual telah digambarkan berdasarkan literatur. Penelitian ini menemukan bahwa aspek halal- haram dalam Syariah Islami memiliki pengaruh yang sangat positif terhadap persepsi para konsumen muslim terkait dengan sistem pengurangan pajak. Sebagai tambahan, kesadaran hukum dan pengetahuan tentang pajak dan zakat memiliki pengaruh positif yang signifikan pada persepsi konsumen muslim yang terkait dengan sistem ini. Sehubungan dengan terbatasnya literatur yang tersedia terkait dengan masalah ini, penelitian ini menawarkan temuan- temuan yang menarik yang dapat mendukung pengembangan praktik- praktik di negara- negara muslim dan untuk memahami persepsi para konsumennya terkait dengan sistem pengurangan pajak.